Rancang Bangun Aplikasi Manajemen Fixed Asset Sistem Informasi Rumah Sakit Studi Kasus Rsia Bunda Aliyah - Daud Rifki Gunawan; Feri Sulianta fs (Ridwan Institute, 2022)
Mother and Child Hospital Mother Aliyah is a special type B mother and child hospital located at Jalan Pahlawan Revolution 100, Pondok Bambu Village, Duren Sawit District, East Jakarta Municipality. the results of observations made, fixed asset management is still done manually, resulting in a work process that is less effective and inefficient in managing existing fixed assets. The purpose of this research is to improve the workflow that is currently running, it is necessary to develop a Fixed Asset Management Application at the Bunda Aliyah RSIA Hospital. The development of this information system application uses a structured methodology of the Waterfall Model (Waterfall Modeling). This development starts from the Requirements stage, Design stage, process specifications, data dictionary, Implementation stage, Integration and System Testing, and Operation and Maintenance.